Evaluasi Gameplay Pada Game Dreadout Dan Outlast 2 Menggunakan Metode Heuristic For Evaluating Playability - Abimanyu Prayuda I. H. Alfianto; Eriq Muhammad Adams Jonemaro; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Dreadout is game with horror genre developed by Digital Happiness from Indonesia. Outlast 2 is one of the best horror genre game with high Metacritic score and has many positive reviews on Steam. In both games there are elements that make players interested in playing it. One element that makes players interested is, Gameplay. Gameplay is an important element in the process of making games. There are techniques for developing gameplay one of them is Atomic Element of Game. To find out the gameplay in both games is interesting for players, then the evaluation using the method of Heuristic For Evaluating Playability which is a way used for evaluation on the game. Evaluation aims to get the player's interest factor in the game's gameplay. With the evaluation results can be made recommendations Atomic Elements of Game is better for both games based on the wishes of respondents.